FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PERPINDAHAN MEREK PADA KONSUMEN (Studi Kasus produk IndiHome di Wilayah Bandung Raya) - Rahma Wulan Hijriany; Siti Samsiyah Purwaningsih (Applied Business and Administration Journal, 2022)
The rapid development of technology aligns with the development of the internet, which keeps growing on a daily bases, resulting in the proliferation of internet service providers today. This is due to the high public demand for internet access, which has turned it into a "primary" need and a separate lifestyle, especially for people in the Bandung Raya area. Consumer brand switching behavior cannot be avoided in the face of increasing competition for internet service providers. One of the companies in Indonesia that provides internet provider services is PT Telkom Indonesia with IndiHome products. The purpose of this study is to identify the factors that cause brand switching behaviour between IndiHome customers in the Bandung Raya area and to know which has the highest and lowest dimension contribution based on the factors that cause brand switching behaviour. This study's population consists of customers who have switched from IndiHome products to other products and live in the Bandung Raya area. The sampling technique used is non-probability sampling, specifically the purposive method (according with goal of this study) by distributing questionnaires to customers who have switched from IndiHome to other internet service providers. The data in this study was analyzed quantitatively using a descriptive analysis method. Based on the results of the research through 101 respondents, they "agree" that the factors of pricing, inconvenience, competitor attractiveness, and failure of core services contribute to brand switching behaviour. The highest contribution to brand switching behaviour is the dimension of core service failures, while the lowest contribution is the dimension of inconvenience.